The potential association of peripheral inflammatory biomarkers in patients with papillary thyroid cancer before radioiodine therapy to clinical outcomes - Cao, Jingjia; He, Xiaoxi; Li, Xiao; Sun, Yaru; Zhang, Wei; Li, Yuyang; Zhu, Xiaolu (Frontiers in Endocrinology, 2023)
Neutrophil-lymphocyte ratio (NLR), markers-lymphocyte-to-monocyte ratio (LMR), and platelet to-lymphocyte ratio (PLR) have potential roles as prognostic biomarkers in various cancers. The study was evaluated to investigate the predictive value of the peripheral inflammatory biomarkers in patients with papillary thyroid carcinoma (PTC) before radioiodine therapy to the response of clinical outcomes.We retrospectively analyzed the patients diagnosed with PTC at the Second Hospital of Shandong University between September 2018 and January 2020. Patients were divided into low 2 and high inflammatory biomarker groups based on median values. The area under the receiver operating characteristic curves (ROC) and logistic regression were used to explore the potential risk factors.Results: A total of 692 patients were enrolled, which included 197 (28.4%) males and 495 (71.6%) females. The median values of NLR, LMR and PLR of these patients were 1.7 (range 0.3-5.7), 7.1 (range 1.1-23.4) and 137.6 (range 27.6-497.5), respectively, and the mean values were 1.95±0.82, 7.4±2.5 and 148.7±54.8, respectively. Compared to the lower PLR group, the higher group was significantly associated with gender, tumor size, N stage and thyroglobulin level (P＜0.05). At the end of follow-up, 75.5% (523/692), 13.3% (91/692), 4.5% (31/692), and 6.7% (47/692) of patients were evaluated as excellent response (ER), indeterminate response (IDR), structural incomplete response (SIR), and biochemical incomplete response (BIR) respectively. In term of clinical outcomes, the NLR, LMR and PLR showed relatively low discriminative power (P≥0.05).We found that higher PLR values was associated with poor clinicopathological features in PTC. However, the peripheral inflammatory indicators (NLR, LMR and PLR) may be insufficient to predict short-term clinical outcomes of patients with radioiodine therapy.